ANALISIS PENGARUH INVESTASI, OPERASI MONETER DAN ZIS TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Khairina Tambunan (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2016)
This study seeks to verify and explain the influence of investment, monetary operations and alms to the Indonesian economy. While the method used is multiple linear regression analysis method with variables that conventional mutual funds, Islamic mutual funds, Bank Indonesia Sharia Deposit Facility (FASBIS), the amount of zakat, donation, and alms (ZIS) and Indonesia's real Gross Domestic Product. The data used in this research is time series data in the period from January 2013 - December 2015. The study found that simultaneously showed that about 97.2% variable konvensonal mutual funds, Islamic mutual funds, FASBIS, and zakat affect Indonesia's GDP the period January 2013- December 2015, while 2.8% is explained by other factors. Partially conventional mutual funds, FASBIS, and alms giving effect to real GDP Indonesia, while Islamic mutual funds do not look real to real GDP Indonesia.